1999
DOI: 10.1046/j.1365-2222.1999.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptidase activities in serum and bronchoalveolar lavage fluid from allergic asthmatics — comparison with healthy non‐smokers and smokers and effects of inhaled glucocorticoids

Abstract: We conclude that reduced peptidase activities in serum or BAL fluid can be found in healthy smokers, but not in allergic asthmatics, and that inhaled glucocorticoids do not affect peptidase activities in BAL fluid or serum of asthmatics. Our results do not support the hypothesized dysfunction of peptidases in the asthmatic airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 42 publications
1
17
1
Order By: Relevance
“…DPPIV activities reduced in smokers and increased in diabetics have already been reported. 11,12 This correlates with observations in patients receiving ACEI and raises the question of whether the higher frequency of smoking subjects developing ACEI-induced angioedema may be a consequence of DPPIV decrease. Thus, the role of SP may be more prominent than suspected previously.…”
Section: Dppiv Activity and Acei-induced Angioedemasupporting
confidence: 70%
“…DPPIV activities reduced in smokers and increased in diabetics have already been reported. 11,12 This correlates with observations in patients receiving ACEI and raises the question of whether the higher frequency of smoking subjects developing ACEI-induced angioedema may be a consequence of DPPIV decrease. Thus, the role of SP may be more prominent than suspected previously.…”
Section: Dppiv Activity and Acei-induced Angioedemasupporting
confidence: 70%
“…Van der Velden and colleagues did not observe any differences in the peptidase activities between allergic asthmatics and healthy nonsmokers. Because the DP4-like activities in the BAL fluid and the lung might at least be partially released by activated CD4-positive T-cells (Juillerat-Jeanneret et al 1997), they explained their observations with an unaltered T-cell number in the allergic asthmatics (van der Velden et al 2000). Corresponding to the abovedocumented upregulated DP4-like activities in the lung and BAL fluid of rats after asthma induction, our previous studies showed an elevated number of activated T-cells after asthma induction in this rat model (Skripuletz et al 2007).…”
Section: The Journal Of Histochemistry and Cytochemistrymentioning
confidence: 78%
“…The results established elevated serum DPP-IV activity as a clinically useful marker of cholestasis and demonstrate that DPP-IV levels do not change in metastatic bone disease (Lakatos et al, 1999;Perner et al, 1999) nor in allergic asthmatics, inhaling glucocorticoids or not (Van Der Velden et al, 1999). Higher activities were also found in serum of patients with osteoporosis, probably related to its severity (Gotoh et al, 1988).…”
Section: Discussionmentioning
confidence: 91%
“…Higher activities were also found in serum of patients with osteoporosis, probably related to its severity (Gotoh et al, 1988). However, reduced peptidase can be found in healthy smokers (Van Der Velden et al, 1999), alcoholdependent (Maes et al, 1999) and major depressive (Maes et al, 1997) donors. These last drops are also in agreement with an impaired immune response.…”
Section: Discussionmentioning
confidence: 97%